Évaluation de l’impact du trafic sur les régions traversées - Raphaëlle Arnaud (Développement Durable et Territoires)
The advent of new preoccupations and objectives related to sustainable development incites to develop new evaluation methods. These regard the development of indicator systems to measure progresses realised to reach these objectives. In this context, this contribution presents a study on the elaboration of a methodology developed to evaluate the result (impact) of a modal (railway/road) and/or spatial (different corridors) split of transalpine freight traffic, on the sustainability of the transited alpine areas. This generic method, which is applied to the transalpine freight traffic and tested on the Swiss territory, is developed to determine the feasibility of its application on the whole alpine segment (Fréjus-Brenner).